Analysis Of Student Sentiment On Lecturers Teaching Using The Fuzzy Tsukamoto Method - Wira Apriani; Sulastri Sulastri; Finna Maulidina (Jurnal Info Sains : Informatika dan Sains, 2023)
Analysis of student sentiment on lecturer teaching performance This study aims to analyze student sentiment on lecturer teaching performance in a good university. The method used in this research is sentiment analysis using the Fuzzy Tsukamoto Method. The data were obtained from the results of a questionnaire conducted on students regarding the teaching performance of lecturers in the last semester. The data is then processed and analyzed using a classification algorithm to classify student sentiment into positive, negative, or neutral towards lecturer teaching performance. is student sentiment towards lecturers, from the teaching quality testing data = 2 positive words (8), Material Availability = 2 neutral words (7), Student and lecturer interaction = 1 negative word (4), Lecturer Feedback Quality = 2 negative word (3) from the input the output result is a value of 3 and is in the negative set, so the result of the test is negative sentiment